Regulation of Algorithmic Disclosure: Challenges, Requirements, and Regulation - Ren, Xin (International Journal of Computer Science and Information Technology, 2024)
The rapid development and wide application of artificial intelligence technology greatly facilitates people’s lives, and also arouses attention to the transparency, fairness and explainability of algorithmic decision making, and algorithmic disclosure has become an important decoding of such problems. However, algorithmic disclosure itself also has certain challenges. First of all, the development level of technology is the basis of disclosure behavior and supervision of algorithmic disclosure, which greatly affects the effect of algorithmic disclosure. Secondly, under the trend of cost-effectiveness, different entities show insufficient motivation for algorithm disclosure and supervision. In the algorithm disclosure, there are multiple purposes such as technology development and rights protection, which need to be balanced; In addition, the privacy and security issues involved in algorithmic disclosure also bring challenges to disclosure behavior. In this regard, we should make clear the rules of algorithm disclosure and improve the supervision of algorithm disclosure. On the one hand, through the clarification of the disclosure principle, the object and the form and content, the platform and other subjects are clearly guided. On the other hand, it also makes up for the deficiency of single supervision and increases the efficiency of algorithm disclosure by means of multiple regulatory bodies and regulatory methods.